Insect Diversity in Horticultural Crops Frequently Sprayed with Pesticides (Biosaintifika: Journal of Biology & Biology Education, 2026)
Insect diversity reflects the complex interaction between insects and their environment, as demonstrated by their various functional roles, including pollinators, predators, parasitoids, decomposers, and phytophage. In horticultural ecosystems, insect diversity can indicate environmental stability because insects help maintain ecosystem balance and support crop productivity through various ecological interactions. This study aimed to analyze insect diversity in horticultural crops frequently sprayed with pesticides located in Bawen, Semarang Regency, Indonesia. The research was conducted in horticultural plantations to collect insect diversity data using hand-collecting and pitfall trap methods. The insect diversity data were analyzed using the Shannon-Wiener diversity index (H), the evenness index (E) and Simpson's dominance index (D), and Environmental factors. The results show that 4,142 insects were found in this study, belonging to 8 orders, 43 families, and 69 species. The insect diversity index indicates a highly diverse insect community with relatively even distribution of individuals among species and low species dominance, suggesting that the horticultural crops in Bawen are ecologically stable, despite routine pesticide application. Seasonal transition and pesticide use show limited variation in their influence on insect diversity. This study supports the Sustainable Development Goals (SDGs), particularly SDG 15 (Life on Land), by conserving insect biodiversity in horticultural ecosystems.